2018
DOI: 10.1515/ijamh-2018-0078
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of hematological parameters for differential diagnosis of endometriomas in adolescents/young adults and older women

Abstract: Background Inflammatory processes have been considered to be involved in the pathogenesis of endometriosis. However, the predictive role of inflammatory hematological parameters in endometriosis is not clear. The aim of this study was to analyze the clinical value of hematologic markers in the differential diagnosis of endometriomas in younger and older reproductive age women. Materials and methods A retrospective chart review was done for 502 patients who underwent surgery: 267 with endometriomas (endometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Three studies showed that neutrophil count was higher in patients with endometriosis than in women without the disease [9,23,31]. On the other hand, three studies showed no significant difference among groups, either when considering OMAs or in non-OMA patients [14,25,28]. Importantly, our present study confirmed a significantly higher neutrophil count in patients with endometriosis.…”
Section: Systemic Inflammatory Markers In Endometriosis Patientssupporting
confidence: 74%
See 4 more Smart Citations
“…Three studies showed that neutrophil count was higher in patients with endometriosis than in women without the disease [9,23,31]. On the other hand, three studies showed no significant difference among groups, either when considering OMAs or in non-OMA patients [14,25,28]. Importantly, our present study confirmed a significantly higher neutrophil count in patients with endometriosis.…”
Section: Systemic Inflammatory Markers In Endometriosis Patientssupporting
confidence: 74%
“…Among six studies investigating PLR [9,14,24,25,28,30], results obtained were more consistent. Four groups reported a significantly higher PLR in women with endometriosis [9,24,28,30]. In our previous case-control study [14], considering the various manifestations of endometriosis separately, we found that women with stage I to II endometriosis had significantly higher PLR than those with stage III to IV disease.…”
Section: Systemic Inflammatory Markers In Endometriosis Patientsmentioning
confidence: 57%
See 3 more Smart Citations